(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The study of the work of composers whose works contain folklore is relevant in modern musical knowledge. Renat Akhmetovich Yenikeev (1937 - 2020) is a Tatar composer, in his work a special place was occupied by work with musical folklore, and not only Tatar, but, much more broadly, the folklore of the Turkic peoples. The desire to understand the origins of the proto-culture of their people destroyed the barriers of narrow national tendencies, allowed to recreate the integral Turkic world in the piano embodiment. The piano cycle “Turkic tunes” consists of four issues and includes 100 pieces for piano on Kazakh, Kyrgyz, Uzbek, Gagauz, Nugai, Tatar, Bashkir and other themes. The purpose of the article is to promote this work among musicians-performers of the Turkic republics, to expand their performing repertoire, enriching the national ear with new images, melodies and rhythms.